Acute kidney injury after non-cardiovascular surgery: risk factors and impact on development of chronic kidney disease and long-term mortality. (3rd October 2018) - Pourafkari, Leili; Arora, Pradeep; Porhomayon, Jahan; Dosluoglu, Hasan H.; Arora, Preksha; Nader, Nader D.
Abstract: Objective: To identify factors associated with acute kidney injury (AKI) and its progression to chronic kidney disease (CKD) in a non-cardiac/non-vascular surgery setting. Methods: This study examined the Veterans Affairs Surgical Quality database for surgical entries between 2000–2014. Demographics, comorbidities, laboratory findings and hospital outcomes were assessed. The primary end-point was the occurrence of AKI, defined as an increase of ≥0.3 mg/dL, 48 h post-operatively. Major adverse cardiac event (MACE) was defined as the composite first occurrence of myocardial infarction, cardiac arrest, and death in 30 days (secondary end-point) and was compared between two groups. Rates of progression to CKD in 1 year and long-term survival were examined. Main outcome measures: Occurrence of AKI 48 h post-operatively. Results: AKI was documented in 8.5% of patients. Age, diabetes, and chronic obstructive pulmonary disease, chronic kidney disease, platelet count, serum albumin level, and duration of surgery were identified as independent predictors of AKI. In total, 6.4% patients developed MACE, which was more frequent in patients with AKI ( p  < .001). Age and pre-operative hematocrit <30% were independent predictors of progression to CKD. Pre-operative hematocrit with a cut-off value of 30% was the only modifiable factor to predict the long-term survival. Conclusion: Development of AKI is associated with increased odds of various post-operative complications and long-term renal insufficiency and mortality.